Intra-Industry Trade in Agricultural and Food Products: The Case of Greece prior and during the Debt Crisis - Dimitrios Dadakas (German Journal of Agricultural Economics (GJAE), 2019)
This article examines the evolution of Greek Intra-Industry Trade (IIT) in agri-food products during the period 2002-2016, concentrating on evident changes in IIT shares after the onset of the 2009 Greek debt crisis. The severity of the Greek crisis, which affected the main determinants of IIT, presents a unique opportunity to study producers' reaction and infer on policy targets to assist trade during economic downturns. I concentrate on agricultural and food products, as they have received less attention in the IIT literature and examine IIT through the Grubel-Lloyd index and by separating IIT into Horizontal IIT (HIIT), and high and low-quality Vertical IIT (HVIIT and LVIIT). Results indicate the post-2009 growth of high-quality VIIT exports in products that require a high degree of processing. Panel VAR analysis indicates that negative shocks to GDP have a significant and persistent negative impact on VIIT and HVIIT.
Keywords: 330